Properties of concrete containing crumb rubber and rice husk ash mixing with peat water - Abdurrahman, Habib; Alfikri, Nur; Rijaldo, Arief; Qoryati, Mia; Marpaung, Horas Saut Maringan; Wibisono, Gunawan; Olivia, Monita (Faculty of Engineering Universitas Riau and Applied Materials and Technology Society, 2025)
This study compares the effects of peat water and normal water as mixing and curing water on the properties of crumb rubber and rice husk ash concrete (CR-RHA). The number of crumb rubber and rice husk ash used on the concrete followed the optimum mixture from a previous study, which was 5% and 10%, respectively. The crumb rubber was treated to overcome the lack of adhesion by soaking it in water for 24 hours. Normal concrete (PCC) was also cast as a control. CR-RHA and PCC concrete were mixed and cured using normal and peat water. Compressive strength, tensile strength, and porosity were tested at 3, 7, 14, 28, and 56 days. In general, CR-RHA concrete and PCC concrete showed lower performance when mixed and cured with peat water compared to normal water. Peat water with high acidity decreased the calcium content and developed the amount of pores in concrete, resulting in strength reduction. However, due to the excess pozzolan from rice husk ash, CR-RHA concrete had better resistance as the strength loss was relatively smaller, respectively 11.4% at 28 days and 10.6% at 56 days. Furthermore, CR-RHA concrete showed lower porosity, higher compressive strength, and tensile strength than PCC concrete due to rice husk ash that improved concrete density by generating CSH and crumb rubber that prevented concrete from spalling in an acidic environment. It was also found that compared to the previous study, pre-treated crumb rubber exhibited better mechanical and durability of concrete.